A fully coupled OpenFOAM® solver for transient incompressible turbulent flows in ALE formulation. (3rd April 2017) - Mangani, L.; Buchmayr, M.; Darwish, M.; Moukalled, F.
ABSTRACT: In this article, the previously developed single block fully coupled algorithm [1, 2 ] for solving three-dimensional incompressible turbulent flows is extended to resolve transient flows in multiple rotating reference frames using the arbitrary Lagrange–Euler (ALE) formulation. Details on the discretization of ALE terms along with a recently developed extension to the conservative and fully implicit treatment of multi-block interfaces into three-dimensional space are presented. To account for turbulence, the k ω − SST turbulence model in ALE formulation is solved using Navier–Stokes equations. This multi-block transient coupled algorithm is embedded within the OpenFOAM® Computational Fluid Dynamics (CFD) library, and its performance evaluated in a real case involving a turbulent flow field in a swirl generator by comparing numerical predictions with experimental measurements.